Pengaruh Ukuran Perusahaan, Financial Leverage, Profitabilitas dan Nilai Saham pada Tindakan Perataan Laba - Sigit Adi Nugroho; Yeni Kuntari; Triani Triani (Jurnal Ilmiah Aset, 2021)
The purpose of this study was to analyze the factors that affect income smoothing. The factors examined in this study were firm size, financial leverage, profitability and stock value as the independent variables while income smoothing as the dependent variable. The samples were 11Automotive and Components companies listed on the Indonesia Stock Exchange (IDX) that submitted financial reports consistently in 2014-2018 period. The data used in this study were secondary data using a purposive sampling method. The data analysis in this study used logistic regression analysis. The test results showed that firm size had a significant effect on income smoothing while financial leverage, probability and stock value had no effect on Income smoothing. Simultaneously firm size, financial leverage, profitability and stock value had a significant effect on Income Smoothing of Automotive and Components Companies listed on the Indonesia Stock Exchange in 2014-2018.